A mixture of mantle and crustal derived He-Ar-C-S ore-forming fluids at the Baogutu reduced porphyry Cu deposit, western Junggar - Cao, M.; Qin, K.; Li, G.; Evans, Noreen; He, H.; Jin, L. (Elsevier Ltd, 2015)
Most large to huge porphyry Cu deposits (PCDs) are oxidized, making the Baogutu reduced porphyry Cu deposit (RPCD) a relative rarity. CH4-bearing ore-forming fluids formed at several hydrothermal stages, however, their source is still unclear. To address this issue, isotopic investigations of sulfide He-Ar-S and calcite C were conducted. Fluid inclusions hosted in sulfides (arsenopyrite, chalcopyrite and pyrite) showed 3He/4He ratios of 0.06-0.30Ra (Ra is the 3He/4He ratio of air=1.39×10-6), 40Ar/36Ar of 311-405, 40Ar*/4He of 0.06-1.01, and F4He ratios of 902-11,074 (sample BGT-Py 2 yielded a ratio of 100), indicating a predominantly crustal source for the fluids with minor mantle input (less than 5%). The d13C values of carbonate yielded a value of -7.8‰ (n=3), implying that CO2 was probably sourced from mantle or juvenile lower crust. According to the restricted sulfide d34S values, the total S isotopic composition of the hydrothermal system was estimated to be 0.0-0.5‰, suggesting that the sulfur was derived from mantle or lower crust magmatic source. According to the published granitoids Nd isotopic compositions at the Baogutu RPCD, fairly young TDM model ages (450-650Ma) suggest that the granitoids were derived from partial melting of a juvenile basaltic lower crust. Thus, we propose that small proportion of mantle-derived fluids (less than 5%), probably rise up and then mix with the fluids of juvenile lower crust under an extensional tectonic setting, forming the mantle-derived Sr-Nd-Pb-S-C but crustal He-Ar isotopic compositions.